Factors Influencing Consumer Intention and Decision to Purchase Plastic Waste Recycle Machine - Mohammad Baedowy; Ujang Sumarwan; Iwan Setiawan (School of Business, IPB University (SB-IPB), 2020)
About 1.42 million tonnes of plastic waste in Indonesian waters are unable to manage every year. Plastic waste recycling machine may be the solution to this environmental problem. Marketing strategy is required to answer the challenge in the sale of plastic waste recycling machine. This research aims to identify and analyse the factors that influence the interest of purchasing intention and purchasing decision of plastic waste recycling machine manufactured by PT Majestic Buana Group. The research was conducted for eight months from February to September 2019. Primary data were obtained through online questionnaires, while secondary data were gathered from literature, journals, and research reports. This research used purposive sampling, with a sample number of 100 respondents who have purchased the plastic recycling machine from PT. MBG from the last 5 years. Data was then processed using descriptive analysis and Structural Equation Modelling-Partial Least Square (SEM-PLS). The results show that product variables, processes, service quality have a significant influence on the purchase interest while product variables, service quality and company reputation significantly affects purchasing decisions. Keywords: marketing mix, SEM PLS, purchasing intention, plastic waste, recycling machine